2018
DOI: 10.1109/tcomm.2018.2865732
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signal Modeling of a Partially Counting Absorbing Spherical Receiver

Abstract: To communicate at the nanoscale, researchers have proposed molecular communication as an energy-efficient solution. The drawback to this solution is that the histogram of the molecules' hitting times, which constitute the molecular signal at the receiver, has a heavy tail. Reducing the effects of this heavy tail, inter-symbol interference (ISI), has been the focus of most prior research. In this paper, a novel way of decreasing the ISI by defining a counting region on the spherical receiver's surface facing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…For an MCvD channel with memory L, theoretical BER evaluation ideally requires 2 L cases' error probability evaluations. Stemming from the complexity of such an operation, various performance metrics including signal-to-interference ratio (SIR) [24], signal-to-interference-and-noise ratio (SINR) [25], and signal-to-interference difference (SID) [15] have been proposed in the literature. Inspired by the existence of a correlation between BER and the ratio between a molecular signal's mean and standard deviation [26], we propose an alternative performance metric to evaluate the signal quality in this work.…”
Section: System Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…For an MCvD channel with memory L, theoretical BER evaluation ideally requires 2 L cases' error probability evaluations. Stemming from the complexity of such an operation, various performance metrics including signal-to-interference ratio (SIR) [24], signal-to-interference-and-noise ratio (SINR) [25], and signal-to-interference difference (SID) [15] have been proposed in the literature. Inspired by the existence of a correlation between BER and the ratio between a molecular signal's mean and standard deviation [26], we propose an alternative performance metric to evaluate the signal quality in this work.…”
Section: System Modelmentioning
confidence: 99%
“…Note that SINAR also takes the number of transmitted molecules (M ) into account, which is a key difference when compared to SIR [24] and SID [15] metrics. In addition, the fact that M is used in first order makes physical sense, since the number of transmitted molecules is considered to be directly proportional to energy required to synthesize and/or emit them [27].…”
Section: System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired from the nature of diffusion, it is shown that using a partially-counting receiver based on angular position has beneficial effects in molecular communications [16]. Since molecules move slowly, it takes much higher expected time to move to the part of the receiver, which are far from the transmitter.…”
Section: Angular Dependent Channel Impulse Responsementioning
confidence: 99%